Development of a robotic vehicle complex for wildfire-fighting by means of fire-protection roll screens. (January 2019) - Nikitin, V; Golubin, S; Belov, R; Gusev, V; Andrianov, N
Abstract: Fighting wildfires is one of the most important missions of Russian forest management. The most promising and safe means of fire-fighting are now the robotic fire-fighting vehicle complexes. The NPP "Tenzosensor" is developing a multi-agent robotic vehicle complex for wildfire-fighting by means of fire-protection roll screens, supported by the Ministry of Education and Science of Russia and in cooperation with SPbNIILH and "Avialesohrana" Federal Budget Entities. The scientific missions of the paper are: substantiation of the fleet of the multi-agent robotic complex for wildfire-fighting by means of fire-protection roll screens; substantiation of the structure of the multi-agent remote control system; substantiation of the structure of the poly-joystick based remote control interface. The set goals were achieved by experimental modelling and a theoretical analysis of the results obtained. It is supposed that the performance of the robotic vehicle complex for wildfire-fighting could be equivalent to that of a brigade of 40-60 firemen.